Peningkatan Pertumbuhan dan Hasil Padi Sawah Organik dengan Berbagai Macam Aplikasi Pupuk Hijau Glirisidia - Marti Winarni (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2018)
The object of the study was to obtain the types of application of Glirisidia green manures on the growth and yield of organic rice lowland. The experimental pot experiment was carried out in a randomized block design consisting of one factor and three replications. The treatment factor was 10 various application of Glirisidia leaves. The treatments are: 100% fresh Glirisidia leaves + 0% compost; 60% fresh Glirisidia leaves + 40% compost; 40% fresh Glirisidia leaves + 60% compost; 100% wind-dried Glirisidia leaves + 0% compost; 60% of wind-dried Glirisidia leaves + 40% compost; 40% wind-dried Glirisidia leaves + 60% compost; 100% sun-dried Glirisidia leaves + 0% compost; 60% of the sun-dried Glirisidia leaves + 40% of compost; 40% of the sun-dried Glirisidia leaves + 60% compost; and 0% Glirisidia leaves + 100% compost. The results showed that the various application of Glirisidia leaves increased the grain yield 34, 09% compared to the application of 0% Glirisidia leaf + 100% compost. The grain/ hill of yield could be improved by application of 100% fresh Glirisidia leaves + 0% compost (164,47 g grain/hill), 100% of wind-dried Gliricidia leaves (165,55 g grain/ hill) + 0% compost, or 100% sun-dried Gliricidia leaves + 0% compost (169,14 g grain/ hill).Â Keywordsâ€”: organic rice lowland; green manure; various application of Glirisidia leaves.Â